Approximation of noisy data using multivariate splines and finite element methods. (April 2021) - Lamichhane, Bishnu P; Harris, Elizabeth; Le Gia, Quoc Thong
We compare a recently proposed multivariate spline based on mixed partial derivatives with two other standard splines for the scattered data smoothing problem. The splines are defined as the minimiser of a penalised least squares functional. The penalties are based on partial differential operators, and are integrated using the finite element method. We compare three methods to two problems: to remove the mixture of Gaussian and impulsive noise from an image, and to recover a continuous function from a set of noisy observations.